Using Data in Leadership Practices: Perceptions of High School Principals - Dutcher, Helene (My University, 2011)
Mixed methods were used to examine the views of high school principals collected from surveys and interviews regarding aspects of data-based decision making. The perceptual data gathered from surveys ranked 1) how principals use data in standards-based leadership practices, 2) how principals build capacity for using data in the school, and 3) how districts support principals in using data for school improvement. Comparisons were made for different groups of principals based on the status of the school in terms of Adequate Yearly Progress (AYP). Principals were most frequently using state standardized assessment data to determine the strengths and weaknesses in the curriculum and to analyze student levels of achievement. Principals were engaged less frequently in gathering and using needs assessment data for addressing multicultural and ethnic concerns in the school and community, and for collecting data to develop a school vision that ensures educational equity for all learners. An Analysis of Variance (ANOVA) of three groups of principals revealed a significant difference between perceptions of principals of schools in Needs Improvement (NI) status and principals of schools that have met AYP or schools not in NI status. Compared to the other two groups of principals, the principals of schools in NI status indicated less engagement and support in the three aspects of data-based decision making that comprised the study. Qualitative data enhanced the interpretation of the quantitative findings and further illuminated the impact made by accountability mandates and leadership standards on the behaviors of high school principals.
Keywords: High School; Principals; Adequate Yearly Progress; ANOVA; Standardized Assessment; Leadership